2015
DOI: 10.1016/j.eml.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Strain tunable optics of elastomeric microlens array

Abstract: a b s t r a c tMicrolens arrays (MLAs) have attracted great attention with their important applications in many fields, such as optical communications, organic light emitting diodes (OLEDs), thin film photovoltaic cells, and novel bio-inspired devices. The dynamically tunable MLAs whose optical properties can be changed in a controllable manner are especially desirable in some recent developments. In this study, a very simple tuning method via mechanical stretching is proposed to tune the optics of elastomeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In our experiment, the compressive strain ε pre is caused by Poisson's effect when a tensile strain ε applied is applied along the horizontal direction in Figure a. Since PDMS is nearly incompressible, the compressive strain ε pre in Equation can be related to the tensile strain ε applied as εpre = 111+εapplied…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In our experiment, the compressive strain ε pre is caused by Poisson's effect when a tensile strain ε applied is applied along the horizontal direction in Figure a. Since PDMS is nearly incompressible, the compressive strain ε pre in Equation can be related to the tensile strain ε applied as εpre = 111+εapplied…”
Section: Resultsmentioning
confidence: 97%
“…Micro‐ and nanostructured soft surfaces offer a new strategy to dynamically tune optical properties by changing the surface topography without affecting the bulk properties . Recently, surface wrinkling has become a very cost‐effective, facile technology to reversibly control the surface topography, which inspired a wide range of applications such as thin‐film properties measurement, tunable adhesion and wettability, stretchable electronics, and optical materials/devices . Some more recently studies have demonstrated that surface wrinkling can also be used to prepare large‐area smart windows capable of controlling the light transmittance by means of micro‐ and nanopillar arrays on wrinkled elastomers, crumpling of metallic nanofilms, graphene films, and graphene oxide films on elastomeric substrates and silica nanoparticle‐embedded elastomer composite .…”
Section: Introductionmentioning
confidence: 99%
“…In the current bilayer film, the compressive strain ε pre is caused by Poisson's effect when a mechanical strain ε applied is applied on the film. Since PDMS is nearly incompressible, the ε pre can be related to mechanical strain ε applied asεpre=111+εapplied…”
Section: Resultsmentioning
confidence: 99%
“…Other researchers have built systems with deformable lens arrays to tune the focal length. Li et al [16] conducted a finite element analysis of a lens array placed in tension and studied the corresponding increase in focal length of the lenses in the lens array. Chandra et al [7] built concave and convex elastic microlens arrays whose focal lengths are tunable by stretching.…”
Section: Related Workmentioning
confidence: 99%
“…However, the lens array is attached to the mechanism such that its thickness will be unconstrained. As explored in the literature [12,11,16,7], when a lens array is stretched the shape of the individual lenses in the array will change. This change in shape will impact the imaging properties of the lenses.…”
Section: The Mechanical Principles Of Stretch Imagingmentioning
confidence: 99%